2022
DOI: 10.1108/jfep-06-2021-0162
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting financial inclusion-stability nexus: cross-country heterogeneity

Abstract: Purpose This paper aims to investigate the debated nexus of financial inclusion (FI) and financial stability (FS) in a comprehensive way, with several indicators of FI, considering nonlinearity and cross-country heterogeneity. Design/methodology/approach The authors introduce several indexes for FI by applying principal component analysis (PCA) and explore their impact on stability for a sample of 108 countries and subsamples based on income grouping as well as for pre- and post-crisis episodes over the peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 47 publications
1
3
0
Order By: Relevance
“…San Marino ranks as the most financially inclusive country in our sample, with an index value of 0.517. Our result is in agreement with that of Saha and Dutta (2022), who found San Marino to be the most financially inclusive country with an average index value of 0.96 and 1, respectively. According to the financial access survey (FAS) portal (International Monetary Fund 2019), the indicator of bank branches shows that San Marino has little overbanking; thus, its number of branches per 100,000 adults is the highest in Europe.…”
Section: Variablesupporting
confidence: 93%
“…San Marino ranks as the most financially inclusive country in our sample, with an index value of 0.517. Our result is in agreement with that of Saha and Dutta (2022), who found San Marino to be the most financially inclusive country with an average index value of 0.96 and 1, respectively. According to the financial access survey (FAS) portal (International Monetary Fund 2019), the indicator of bank branches shows that San Marino has little overbanking; thus, its number of branches per 100,000 adults is the highest in Europe.…”
Section: Variablesupporting
confidence: 93%
“…Fourth, financial inclusion helps the monetary authority control inflation (Mbutor and Uba, 2013; Mehrotra and Nadhanael, 2016). At the same time, financial inclusion also causes financial stability and contributes to growth indirectly (Sethi and Sethy, 2019; Saha and Dutta, 2022; Sethy and Goyari, 2022; Bhatter and Chhatoi, 2023). In contrast, Sahay et al (2015) reported financial inclusion doesn't guarantee financial stability.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Global findex survey Irfan et al (2022) described that 20% of adults in developing countries cite distance as a reason for not having a bank account. Saha and Dutta (2022) stated that financial inclusion is a lack of outreach and coverage. Language barrier: one significant barrier for rural areas is language barriers (Karliner et al, 2011).…”
Section: Distance Barriersmentioning
confidence: 99%